CGIAR’s potential tangible contribution to continued Article 6.8 implementation - Vallarino, Eliza J. (2024)
At COP29, the UNFCCC Subsidiary Body for Scientific and Technological Advice has forwarded decision text on Article 6.8 of the Paris Agreement to the Conference of the Parties for the latter’s consideration and adoption. Based on a quick analysis of the document, CGIAR expects to continue participating in the Article 6.8 space during the second phase of implementing the work program.